2019
DOI: 10.3390/toxins11070380
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Polarization Immunoassay for the Determination of T-2 and HT-2 Toxins and Their Glucosides in Wheat

Abstract: T-2 and HT-2 toxins and their main modified forms (T-2 glucoside and HT-2 glucoside) may co-occur in cereals and cereal-based products. A fluorescence polarization immunoassay (FPIA) was developed for the simultaneous determination of T-2 toxin, HT-2 toxin and relevant glucosides, expressed as sum. The developed FPIA, using a HT-2-specific antibody, showed high sensitivity (IC50 = 2.0 ng/mL) and high cross-reactivity (100% for T-2 toxin and 80% for T-2 and HT-2 glucosides). The FPIA has been used to develop tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For example, Lippolis and colleagues have developed a portable FP analyzer for the simultaneous determination of T-2 toxin, HT-2 toxin, and relevant glucosides in wheat [ 52 ]. Antibody used in the study showed high sensitivity (IC50 = 2.0 ng/mL) and cross-reactivity (100% for T-2 toxin and 80% for T-2 and HT-2 glucosides).…”
Section: Advance Multi-mycotoxin Immuno-based Analysismentioning
confidence: 99%
“…For example, Lippolis and colleagues have developed a portable FP analyzer for the simultaneous determination of T-2 toxin, HT-2 toxin, and relevant glucosides in wheat [ 52 ]. Antibody used in the study showed high sensitivity (IC50 = 2.0 ng/mL) and cross-reactivity (100% for T-2 toxin and 80% for T-2 and HT-2 glucosides).…”
Section: Advance Multi-mycotoxin Immuno-based Analysismentioning
confidence: 99%
“…Developments of the singe-reagent FPIA include Lippolis et al on the simultaneous determination of several mycotoxins in wheat [ 13 ], Mi et al on multiple determination of (fluoro)quinolone antibiotics in foodstuffs [ 14 ], and Eremin et al on the high throughput determination of aromatic compounds [ 15 ].…”
Section: Modes Of Fpiamentioning
confidence: 99%
“…Recently such strips have been adapted to test for multiple mycotoxins that include T-2 toxin [ 19 , 20 , 21 ]. Antibody-based biosensors for T-2 and HT-2 have also been reported [ 22 , 23 , 24 ], as well as a fluorescence polarization immunoassay [ 25 ] and aptamer-based tests [ 26 , 27 ]. Current trends in immunoassays for mycotoxin detection were reviewed by Nolan et al [ 28 ].…”
Section: Introductionmentioning
confidence: 99%